Cumulative network meta-analyses, practice guidelines, and actual prescriptions for post-menopausal osteoporosis: a meta-epidemiological study - Kataoka, Y; Luo, Y; Chaimini, A; Cipriani, A; Miss ELIZABETH THOMAS (Springer Nature, 2020)
Purpose: To compare the results of cumulative network meta-analyses (NMAs) with the recommendations in post-menopausal osteoporosis practice guidelines and actual prescribing practices in the US.